Electrocatalytic Self-Coupling of N-Heterocyclic Amides for Energy-Efficient Bipolar Hydrogen Production - Ma, Yuqiang; Li, Meng; Zhang, Dandan; Wang, Cihang; Li, Yu; Zhao, Zihang; Mu, Xiaogang; Hu, Jun; Hu, Xiang; Li, Jiachen; Ma, Haixia; Wen, Zhenhai (Nano-Micro Letters, 2026)
This study proposes a green electrochemical strategy for addressing the high-energy-barrier oxygen evolution reaction (OER) in traditional overall water splitting. Leveraging the thermodynamic advantages of N–H bond activation/cleavage and N–N coupling processes, the 3,5-diamino-1,2,4-triazole (DAT) oxidative coupling reaction (DATOR) has been introduced to replace the high-energy-barrier oxygen evolution reaction (OER). This substitution enables low-energy-consumption hydrogen production while simultaneously yielding high-value azo energetic materials. Furthermore, to enhance electron and atom economy, the anodic DATOR process allows the hydrogen radicals (H*) generated from amine dehydrogenation to chemically combine via the Tafel process, producing hydrogen gas. By constructing coupling system with Pts,n@NiS2@CC cathode and CuO/CF anode, the operating voltage of the system was significantly reduced (0.96 V@10 mA cm− 2), which was 680 mV more energy efficient than conventional water electrolysis (1.64 V). In situ spectroscopy and theoretical calculations indicate that the anode DATOR generates DAAT through the N–H bond cleavage and N–N coupling path mediated by hydroxyl radicals (OH*), while releasing hydrogen gas. The coupling system has been operating stably for more than 300 h at an industrial-grade current density. This research provides new ideas for dual-electrode hydrogen production and green electrosynthesis of functional materials, with significant energy and economic benefits. Highlights: 1 Replacing anodic oxygen evolution reaction with 3,5-diamino-1,2,4-triazole oxidative coupling enables ultra-low-voltage (0.96 V @10 mA cm− 2) dual-electrode H2 production and simultaneous synthesis of energetic 5,5′-diamino-3,3′-azido-1H-1,2,4-triazole (DAAT), achieving 35.8% energy savings. 2 A Pt single-atom/nanoparticle hybrid on NiS2 nanosheets (Pts,n@NiS2@CC) exhibits exceptional alkaline hydrogen evolution reaction performance and stability via optimized H* adsorption. 3 Anodic DAAT formation proceeds via an OH*-mediated N–N coupling pathway, enabling stable (> 300 h @500 mA cm− 2), industrial-scale bipolar H2 production coupled with green DAAT synthesis in an anion-exchange membrane water electrolyzer.